SHAREHOLDERS’ VALUE CREATION IN THE SUN PHARMA-RANBAXY MERGER: AN EVENT STUDY (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
Mergers and Acquisitions have been the area of  strategic focus for many corporate houses since  the last two decades. It is now a global inorganic  growth strategy to serve a variety of firm  specific objectives like accessing new markets,  foreign strategic assets, trade and supporting  infrastructure and shareholder’s value creation.  The pharmaceutical industry in India witnessed  one of the biggest mergers in its history when  Sun Pharma took over Ranbaxy Laboratories.  The merger failed to create value for the  shareholders of Sun Pharma and considerable  amount of literature has corroborated the fact.  The present study has attempted to gather  statistical evidence to prove the fact of such  failure to create value for the shareholders of Sun  Pharma in an objective manner. Seven valuation  ratios have been considered to measure the  value creation by the merger. The results before  and after the merger have been analysed for the  purpose by way of an event study. The study  has been based on secondary data collected for  a ten-year window from the annual reports of  both Sun Pharma and Ranbaxy laboratories as  well as from Ace Equity © data product. This  study has objectively proved that the acquiring  firm was not able to create enough wealth for  shareholders post acquisition.
Keywords: Sun Pharma; Ranbaxy Laboratories; Value Creation; Valuation Ratio; Event Study